A method for preparing high temperature ceramic colored sand for colored stone metal tiles

The ceramic colored sand prepared through high-temperature melting process combines metal oxide coloring and high-temperature ultraviolet coating to solve the problem of poor stability and easy color fading in high-temperature environments, and achieves the improvement of high-temperature durability, color stability and environmental protection performance.

CN119775824APending Publication Date: 2025-04-08JIANGSU TIANWO NEW ENERGY TECHNOLONY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411967547.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The existing colored sand of colored stone metal tiles has poor stability in high temperature environments, easy color fades, insufficient high temperature resistance, and some production processes have problems with insufficient environmental protection performance.

Method used

Kaolin, feldspar, basalt sand and titanium dioxide are used as basic raw materials to prepare ceramic-textured colored sand through high-temperature melting process, and metal oxides are added as colorants during the melting process, and the surface is coated with a high-temperature anti-ultraviolet coating.

Benefits of technology

It has achieved the improvement of high-temperature durability, color stability and environmental protection performance of colored sand, can remain stable in an environment above 300℃, will not fade for more than 10 years, and it meets the requirements of green building materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119775824A_ABST
    Figure CN119775824A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing high-temperature ceramic colored sand for colored stone metal tiles, comprising the following steps: raw material selection, raw material mixing, grinding treatment, high-temperature melting, cooling and particle forming, screening treatment, surface coating and color control. By selecting kaolin, feldspar, basalt sand and titanium dioxide as main raw materials, and melting treatment under high temperature conditions of 1200°C-1400°C, colored sand particles with ceramic texture are prepared. Metal oxide colorants such as iron oxide, copper oxide, cobalt oxide or manganese oxide are added during the melting process to achieve high-temperature fixation of multiple colors. After screening, the particle size is controlled at 18-36 mesh, and the surface is coated with an environmentally friendly anti-ultraviolet coating, which improves the weather resistance and decorativeness of the colored sand. The high-temperature ceramic colored sand prepared by the present invention has high density and low water absorption, is suitable for the surface layer of colored stone metal tiles, and has the characteristics of low cost, simple process and excellent environmental protection performance, and can be widely used in the field of building decoration materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing high-temperature ceramic colored sand for colored stone metal tiles. Background Art

[0002] As a new type of building roof material, colored stone metal tiles are widely used in modern buildings due to their lightness, beauty and durability. The surface colored sand, as a key component, not only directly affects the decorativeness of the colored stone metal tiles, but also significantly affects its service life and weather resistance. However, the colored sand on the market is mainly divided into natural sand and artificial colored sand, which has the following shortcomings:

[0003] Limitations of natural sand: Due to its unstable source, irregular particle shape and uneven particle size distribution, it is difficult to achieve batch-to-batch consistency. At the same time, its stability in high temperature environments is poor, and it is prone to powdering or peeling, which reduces the durability of colored stone metal tiles.

[0004] Disadvantages of artificial colored sand: Although artificial colored sand overcomes some of the shortcomings of natural sand, it generally has the following problems:

[0005] Colors fade easily: Most artificial colored sands use a low-temperature coating process, and the coating is difficult to maintain durability under ultraviolet rays, high temperatures and other environments.

[0006] Insufficient high temperature resistance: Many artificial colored sands are prone to discoloration or performance degradation after high-temperature roasting, which limits their use in extreme environments.

[0007] Poor environmental performance: The colorants and bonding materials used in some production processes may contain harmful substances and do not meet the environmental protection requirements of modern building materials.

[0008] In view of this, developing a ceramic colored sand that is durable in high temperature, stable in color, environmentally friendly and has a moderate production cost to meet the use needs of colored stone metal tiles in a variety of complex environments has important technical value and market significance. Summary of the invention

[0009] The purpose of the present invention is to solve the above-mentioned deficiencies in the prior art and to provide a method for preparing high-temperature ceramic colored sand for colored stone metal tiles with convenient connection.

[0010] A method for preparing high-temperature ceramic colored sand for colored stone metal tiles comprises the following steps:

[0011] Step 1, raw material selection: kaolin, feldspar, basalt sand and titanium dioxide are selected as basic raw materials, among which:

[0012] The mass percentage of kaolin is 60%-70%;

[0013] The mass percentage of feldspar is 20%-30%;

[0014] The mass percentage of basalt sand is 5%-10%;

[0015] The mass percentage of titanium dioxide is 2%-5%.

[0016] Step 2, raw material mixing: mix the above raw materials according to the proportion, and stir evenly to ensure uniform distribution of the components;

[0017] Step 3, grinding: the mixed raw materials are put into a ball mill for grinding for 3-5 hours, and the particle size after grinding is controlled at 60-80 mesh;

[0018] Step 4, high temperature melting: place the ground raw materials in a melting furnace, the melting temperature is 1200℃-1400℃, and the melting time is 2-3 hours;

[0019] Step 5, cooling and particle forming: the molten material is quickly cooled to room temperature, and mechanical crushing or natural cracking is used to form granular ceramic colored sand;

[0020] Step 6, screening: Screen the particles through the sieve, screen the particles with a particle size of 18-36 mesh, and remove the particles that are too large or too small;

[0021] Step 7, surface coating: evenly apply high-temperature anti-ultraviolet coating on the surface of the colored sand, with a coating thickness of 1-5 microns to enhance the weather resistance and color durability of the colored sand;

[0022] Step 8, color control: Add metal oxide colorants during the melting process as needed, including:

[0023] Iron oxide Fe2O3 is used to modulate red, with an addition amount of 2%-5%;

[0024] Copper oxide CuO is used to adjust yellow color, and the addition amount is 1%-3%;

[0025] Cobalt oxide Co2O3 is used to modulate blue, with an addition amount of 1%-2%;

[0026] Manganese oxide MnO2 is used to adjust brown color, and the addition amount is 1%-3%.

[0027] As a further improvement, a high-speed stirring device is used in the raw material mixing process, the stirring speed is 500-1000 rpm, and the stirring time is 30-60 minutes.

[0028] As a further improvement, a controlled atmosphere furnace is used in the high-temperature melting process to avoid high-temperature oxidation and protect the chemical stability of the molten components.

[0029] As a further improvement, the rapid cooling adopts air cooling or water cooling, wherein the cooling time is controlled within 10-30 minutes.

[0030] As a further improvement, the screening process uses multi-layer screens with a screening accuracy of ±5 mesh to ensure uniform particle size.

[0031] As a further improvement, the surface coating material is a non-toxic and environmentally friendly silicone resin coating or a fluorocarbon coating, and is applied by spraying or dipping, and after coating, is cured at a temperature of 150° C.-200° C. for 1-2 hours.

[0032] As a further improvement, the final product density of the ceramic colored sand is 2.5-3.0 g / cm 3 , water absorption rate is less than 0.5%.

[0033] As a further improvement, the type and proportion of metal oxides added during the melting process can be controlled experimentally to achieve specific color requirements.

[0034] A high-temperature ceramic colored sand prepared by the above method, the ceramic colored sand is used for the surface layer of the colored stone metal tile, and has the following characteristics:

[0035] High temperature resistance: able to withstand high temperature environments above 300°C;

[0036] Weather resistance: no fading for more than 10 years under ultraviolet radiation;

[0037] Color uniformity: color difference △E value is less than 3;

[0038] Particle uniformity: Particle size distribution ranges from 18-36 mesh, accounting for more than 95% of the total.

[0039] A metal tile made of high-temperature ceramic colored sand and colored stone prepared by the above method, the metal tile comprising:

[0040] Metal substrate: made of galvanized steel plate or aluminum alloy plate;

[0041] Colored sand layer: high temperature ceramic colored sand is fixed on the surface of the metal substrate by adhesive;

[0042] Adhesive layer: It is a high-temperature and weather-resistant silicone adhesive with a thickness of 0.2-0.5 mm, which can maintain bonding strength in high temperature, strong ultraviolet rays and humid environments.

[0043] In view of the shortcomings of the prior art, the present invention provides a method for preparing high-temperature ceramic colored sand for colored stone metal tiles, and achieves the following beneficial effects by optimizing the raw material formula, preparation process and coloring technology:

[0044] Excellent high temperature resistance: Kaolin, feldspar and basalt sand are used as the main ingredients, and ceramic colored sand is prepared through a high-temperature melting process. The melting temperature is as high as 1200℃-1400℃, which makes the colored sand have extremely high thermal stability and can maintain stable physical and chemical properties in an environment above 300℃ for a long time.

[0045] Color persistence and uniformity: By adding a specific proportion of metal oxides, such as iron oxide and copper oxide, during the melting process, high-temperature fixation of various colors can be achieved, the color difference △E value is less than 3, and it will not fade for more than 10 years under long-term ultraviolet radiation, meeting the requirements of architectural decoration for color uniformity and durability.

[0046] Environmental protection: The raw materials used are all non-toxic and harmless mineral raw materials. The environmentally friendly high-temperature coating technology is adopted to avoid the problem of releasing harmful substances due to the shedding of coating in traditional artificial colored sand, which is in line with the development trend of green building materials.

[0047] High mechanical strength and low water absorption: the density of the prepared ceramic colored sand is 2.5-3.0g / cm 3 The water absorption rate is less than 0.5%, and it is not easy to absorb moisture or cause freeze-thaw damage, thereby improving the weathering resistance of the colored stone metal tile.

[0048] Strong particle uniformity and applicability: Through the screening process, the particle size distribution of the colored sand is strictly controlled at 18-36 meshes. The particle size is uniform and can be well combined with the binder of the colored stone metal tile to improve the density and adhesion of the tile surface layer.

[0049] Multifunctional adaptability: The ceramic colored sand provided by the present invention is not only suitable for colored stone metal tiles, but can also be widely used in the fields of building wall decoration materials, ground anti-slip coatings, etc., and has good market application prospects.

[0050] Cost control and process feasibility: This method adopts a simple raw material ratio and a controllable high-temperature melting process, which reduces the complicated post-processing steps, has low production costs, and the process is easy to achieve large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0051] Figure 1 The invention discloses a flow chart of a method for preparing high temperature ceramic colored sand for colored stone metal tiles. DETAILED DESCRIPTION

[0052] In order to deepen the understanding of the present invention, the present invention will be further described in detail below in conjunction with embodiments and drawings. The embodiments are only used to explain the present invention and do not constitute a limitation on the protection scope of the present invention.

[0053] Example 1

[0054] Raw material selection and proportion: weigh the raw materials according to the following mass percentages:

[0055] Kaolin: 65%;

[0056] Feldspar: 25%;

[0057] Basalt sand: 5%;

[0058] Titanium dioxide: 5%.

[0059] Raw material mixing: Add the above raw materials into a mixing tank according to the proportion, and use a high-speed stirring device to stir at a speed of 800 rpm for 45 minutes to ensure that all components are evenly mixed.

[0060] Grinding treatment: Place the mixed raw materials in a ball mill, add appropriate amount of deionized water as a medium, and perform wet grinding. The grinding time is 4 hours, and the particle size is controlled at 70 mesh, about 200 microns.

[0061] High temperature melting: After the ground mixture is dried, it is placed in an electric melting furnace and melted at a temperature of 1300°C for 3 hours to ensure that the materials react fully to form a dense ceramic texture.

[0062] Cooling and crushing: The molten material is quickly moved to the cooling table and cooled to room temperature by air. The cooling time is controlled within 15 minutes. The cooled material naturally cracks to form particles, and the particle size is adjusted to the rough particle size range by mechanical crushing equipment.

[0063] Screening treatment: Use multi-layer screens to screen the cooled particles, select particles with a particle size of 18-36 mesh, and remove particles larger than 18 mesh and smaller than 36 mesh.

[0064] Surface coating: Immerse the screened ceramic particles in an environmentally friendly high-temperature anti-ultraviolet coating solution and use a spraying device to evenly apply the coating. The coating thickness is controlled at 3 microns and cured in an oven at 180°C for 2 hours.

[0065] Color control: During the high-temperature melting stage, 3% iron oxide Fe2O3 is added as a colorant to form a uniform red ceramic colored sand.

[0066] Final product: The prepared red high-temperature ceramic colored sand has a density of 2.8g / cm 3 The water absorption rate is 0.3%. After UV aging test, it will not fade in 10 years.

[0067] Example 2

[0068] Raw material selection and proportion: weigh the raw materials according to the following mass percentages:

[0069] Kaolin: 60%;

[0070] Feldspar: 30%;

[0071] Basalt sand: 8%;

[0072] Titanium dioxide: 2%.

[0073] Raw material mixing and grinding: the raw materials were mixed according to the steps of Example 1, the grinding time was controlled to be 3 hours, and the particle size was controlled to be 80 mesh, about 180 microns.

[0074] High temperature melting and cooling: the melting temperature was set at 1200°C and the melting time was 2.5 hours;

[0075] The cooling method is water cooling, and the molten material is quickly poured into water to form granular ceramic colored sand.

[0076] Screening and surface coating: Screen the ceramic particles formed after cooling and select 18-36 mesh particles.

[0077] The particle surface is sprayed with a fluorocarbon coating material, and after coating, the coating is cured at a temperature of 200° C. for 1.5 hours.

[0078] Color Control: 2% copper oxide (CuO) is added as a colorant during the melting process to form yellow ceramic colored sand.

[0079] Final product: The prepared yellow ceramic colored sand has been tested to have excellent high temperature resistance and UV resistance, and is suitable for the decorative layer of colored stone metal tiles.

[0080] Example 3

[0081] Raw material selection and proportion: weigh the raw materials according to the following mass percentages:

[0082] Kaolin: 68%;

[0083] Feldspar: 20%;

[0084] Basalt sand: 10%;

[0085] Titanium dioxide: 2%.

[0086] Optimization of melting conditions: After mixing the raw materials, place them in an atmosphere-controlled furnace, melt them at a temperature of 1300°C, and treat them under a nitrogen protection environment to prevent oxidation.

[0087] Color control: 2% cobalt oxide Co2O3 is added during the melting process to produce blue colored sand.

[0088] Control the uniform contact between the oxidant and the molten material to ensure consistent color distribution.

[0089] Cooling and coating: After melting, air cooling is used, and the particle size is controlled at 18-36 mesh after screening. Non-toxic silicone resin is used as the coating material, and it is cured for 1 hour after coating.

[0090] Final product: The density of the prepared blue ceramic colored sand is 2.9g / cm 3 , high temperature resistance up to 350℃, stable color, suitable for building exterior wall coatings and decorative materials.

[0091] The above examples describe in detail the preparation method of the present invention, including specific technical parameters and operation steps of raw material ratio, grinding, melting, cooling, screening and coating. Through these examples, the high temperature resistance, color durability and environmental protection of ceramic colored sand can be significantly improved, and the preparation process is simple and convenient for industrial production.

[0092] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing high temperature ceramic colored sand for colored stone metal tiles, characterized in that: The following steps are involved: Step 1, raw material selection: kaolin, feldspar, basalt sand and titanium dioxide are selected as basic raw materials, among which: The mass percentage of kaolin is 60%-70%; The mass percentage of feldspar is 20%-30%; The mass percentage of basalt sand is 5%-10%; The mass percentage of titanium dioxide is 2%-5%. Step 2, raw material mixing: mix the above raw materials according to the proportion, and stir evenly to ensure uniform distribution of the components; Step 3, grinding: the mixed raw materials are put into a ball mill for grinding for 3-5 hours, and the particle size after grinding is controlled at 60-80 mesh; Step 4, high temperature melting: place the ground raw materials in a melting furnace, the melting temperature is 1200℃-1400℃, and the melting time is 2-3 hours; Step 5, cooling and particle forming: the molten material is quickly cooled to room temperature, and mechanical crushing or natural cracking is used to form granular ceramic colored sand; Step 6, screening: Screen the particles through the sieve, screen the particles with a particle size of 18-36 mesh, and remove the particles that are too large or too small; Step 7, surface coating: evenly apply high-temperature anti-ultraviolet coating on the surface of the colored sand, with a coating thickness of 1-5 microns to enhance the weather resistance and color durability of the colored sand; Step 8, color control: Add metal oxide colorants during the melting process as needed, including: Iron oxide Fe2O3 is used to modulate red, with an addition amount of 2%-5%; Copper oxide CuO is used to adjust yellow color, and the addition amount is 1%-3%; Cobalt oxide Co2O3 is used to modulate blue, with an addition amount of 1%-2%; Manganese oxide MnO2 is used to adjust brown color, and the addition amount is 1%-3%.

2. The method for preparing high temperature ceramic colored sand for colored stone metal tiles according to claim 1, characterized in that: A high-speed stirring device is used in the raw material mixing process, the stirring speed is 500-1000 rpm, and the stirring time is 30-60 minutes.

3. The method for preparing high temperature ceramic colored sand for colored stone metal tiles according to claim 1, characterized in that: A controlled atmosphere furnace is used in the high-temperature melting process to avoid high-temperature oxidation and protect the chemical stability of the molten components.

4. The method for preparing high temperature ceramic colored sand for colored stone metal tiles according to claim 1, characterized in that: The rapid cooling is carried out by air cooling or water cooling, wherein the cooling time is controlled within 10-30 minutes.

5. The method for preparing high temperature ceramic colored sand for colored stone metal tiles according to claim 1, characterized in that: The screening process uses multi-layer screens with a screening accuracy of ±5 mesh to ensure uniform particle size.

6. The method for preparing high temperature ceramic colored sand for colored stone metal tiles according to claim 1, characterized in that: The surface coating material is a non-toxic and environment-friendly silicone resin coating or a fluorocarbon coating, and is applied by spraying or dipping, and after coating, is cured at a temperature of 150° C. to 200° C. for 1 to 2 hours.

7. The method for preparing high temperature ceramic colored sand for colored stone metal tiles according to claim 1, characterized in that: The final product density of the ceramic colored sand is 2.5-3.0g / cm 3 , water absorption rate is less than 0.5%.

8. The method for preparing high temperature ceramic colored sand for colored stone metal tiles according to claim 1, characterized in that: The type and proportion of metal oxides added during the melting process can be controlled experimentally to achieve specific color requirements.

9. High temperature ceramic colored sand prepared according to any one of claims 1 to 8, characterized in that: The ceramic colored sand is used for the surface layer of the colored stone metal tile and has the following characteristics: High temperature resistance: able to withstand high temperature environments above 300°C; Weather resistance: no fading for more than 10 years under ultraviolet radiation; Color uniformity: color difference △E value is less than 3; Particle uniformity: Particle size distribution ranges from 18-36 mesh, accounting for more than 95% of the total.

10. A metal tile made of high temperature ceramic colored sand and colored stone prepared by the method of any one of claims 1 to 8, characterized in that: The metal tile comprises: Metal substrate: made of galvanized steel plate or aluminum alloy plate; Colored sand layer: high temperature ceramic colored sand is fixed on the surface of the metal substrate through adhesive; Adhesive layer: It is a high-temperature and weather-resistant silicone adhesive with a thickness of 0.2-0.5 mm, which can maintain bonding strength in high temperature, strong ultraviolet rays and humid environments.

Citation Information

Cited By

  • Preparation method and application of basalt colored sand

    CN121698595A